Management of severe corneoscleral lacerations - Mertz, Manfred (Zdravniški vestnik, 2002)
Background. Ocular injuries, such as caused by windscreen glass particles or metallic foreign bodies, are very common. in most cases, the corneal laceration is found to be horizontal, and very often it crosses the limbus. Thereby, different tissues of the eyeball are involved simultaneously, e.g. iris root, sclera, outer muscles, trabecular meshwork, ciliary body, pars plana, lens, vitreous etc. For reconstruction and repair, a strong order of procedures is important. After exclusion or location of intraocular foreign bodies by x-ray or ultrasonic methods, the first aim has to be the stabilisation of the globe. First step should be a limbus reconstructing suture, to be followed by Tenon tent, Flieringa ring, scleral exploration (until the very end of the laceration is found, even by muscle surgery), and prefixing of a scleral buckle and/or cerclage if necessary. Not before all these tasks have been fulfilled, the anterior chamber should be entered, and repair of the lens, iris and cornea can be started. The globe being now stabilised in his whole entity, sometimes a primary vitrectomy can be necessary, and also this is the best point of time for the removal of an intraocular foreign body. Post-op treatment should be on in-patient base.
Keywords: Beločnica; Cornea; Eye injuries, penetrating; Injuries; Limbus corneae; oftalmologija; Oko, poškodbe prenetrantne; poškodbe; Rob roženice; Roženica; Sclera; Surgery; therapy; zdravljenje